Functionalized O-carboxymethyl-chitosan/polyethylenimine based novel dual pH-responsive nanocarriers for controlled co-delivery of DOX and genes1. Issue 17 (7th May 2015) - Wang, Mingfang; Liu, Tingxian; Han, Leiqiang; Gao, Wenwen; Yang, Shaomei; Zhang, Na
<x xml:space="preserve">Abstract</x> Dual pH-sensitive CDPD sequentially dissociates the outermost layer, CPN, and shows pH-triggered programmable release of DOX and genes.